2022
DOI: 10.1186/s12940-022-00936-x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of blood lead levels and lead in gasoline: an updated systematic review

Abstract: Background Millions of tons of lead were added to gasoline worldwide beginning in 1922, and leaded gasoline has been a major source of population lead exposure. In 1960s, lead began to be removed from automotive gasoline. Removal was completed in 2021. Objectives To determine whether removal of lead from automotive gasoline is associated with declines in population mean blood lead levels (BPb). Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Epidemiologic investigations have demonstrated that low-level Pb exposure is a risk factor for IQ drops [45,46], cardiovascular disease [47], and hearing loss [48]. According to the World Health Organization, there is no safe blood lead concentration [49]. Various studies showed that Pb could induce cognitive impairment [50][51][52], as well as AD-related neuropathological changes [53], and nerve cell damage is the basis of its pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic investigations have demonstrated that low-level Pb exposure is a risk factor for IQ drops [45,46], cardiovascular disease [47], and hearing loss [48]. According to the World Health Organization, there is no safe blood lead concentration [49]. Various studies showed that Pb could induce cognitive impairment [50][51][52], as well as AD-related neuropathological changes [53], and nerve cell damage is the basis of its pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Humans are exposed to lead via inhalation, ingestion, and skin contact, though through the dermal route, lead poisoning is unlikely [ 26 ]. Due to its toxicity, lead is being phased out of gasoline worldwide [ 27 , 28 ] and reduced in many other areas of previous use. However, exposure is still common, especially in areas close to mining areas [ 29 ], landfills, and industrial or hazardous waste site.…”
Section: Prenatal Exposure To Non-essential (Toxic) Trace Elementsmentioning
confidence: 99%
“…It is worth paying attention to the presence of Pb in the range of 3.78 μg/g ± 3,05 -45.930 ± 2.87. μg/g, which may be characteristic of the dust coming from the fuel stations. It should be taken into account that from the 1960s Pb is removed from gasoline, but removal was completed in the 2021 (Angrand et al 2022). According to the US Environmental Protection Agency, Pb may be from lead paint used (eg, painted fuel pump curb edges) that has deteriorated in the form of chips and dust or from previous renovation activities and has ended up in dust with lead or from the past (eg, dust coming from the vicinity of the road as a result of emissions into the air from vehicles fuelled with leaded petrol) (US EPA 2013).…”
Section: Assessment Of Hazardous Elements Including Environmental Tox...mentioning
confidence: 99%